Spillovers from foreign direct investment in services: Evidence at sub-sectoral level for the Asia-Pacific - Doytch, Nadia (Archīum Ateneo, 2018)
We take a sectoral level approach to analyzing the effects of foreign direct investment (FDI) inflows. We disaggregate FDI first by manufacturing versus services, then within services by financial services, trade services, and business services. We consider the effects of FDI inflows on growth of GDP per capita, then distinguish between growth in manufacturing and services value added per capita. Our data sample comprises 14 Asia Pacific economies for the period 1985–2012 to which we apply a dynamic panel generalized method of moments estimation technique. Services FDI as a whole is found to have a significantly positive impact on GDP growth while manufacturing FDI is found to have no effect. The impetus for growth from services FDI traces to financial services in particular, acting not only directly on service sector output but through manufacturing sector output as well. By contrast, trade services FDI is found to have a significantly negative effect on manufacturing output with no significant effect on services output. Foreign participation in trade services may act to expose domestic manufacturers to international competition and may also lead to domestic consolidation to take advantage of economies of scale.